1998
DOI: 10.1159/000022024
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a Continuous Gamma Irradiation at a Very Low Dose on the Life Span of Mice

Abstract: Background: There is epidemiological evidence that suggests there are beneficial effects of ionizing radiation at low doses. Some experimental studies confirmed this hormetic effect with doses of about 1 cGy/day, but no data concerning very low dose rates are available. Objective: The aim of this study was to determine the life span of mice exposed to very low doses of ionizing radiation. Methods: Six hundred female C57BL/6 mice, 1 month old, were exposed to chronic gamma irradiation at very low dose rates of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
50
0
2

Year Published

1999
1999
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 129 publications
(52 citation statements)
references
References 11 publications
0
50
0
2
Order By: Relevance
“…Thus, multiple low-dose irradiation of human fibroblast cultures extended their lifespan by one-quarter (655); this was not accompanied by specific chromosome abberations or activation of telomerase (655). Furthermore, in a large study involving 900 mice, Caratero et al (656) demonstrated that low-dose irradiation (25-50-fold background) resulted in a significant increase in longevity compared to the control group (673 days compared to 549 days for 50% survival of the starting population). Moreover, in C. elegans, the mutations conferring extended longevity also confer resistance to stress; and the same is true for the recently discovered trk-1 gene, overexpression of which can increase lifespan by up to 100% (657).…”
Section: Stressmentioning
confidence: 99%
“…Thus, multiple low-dose irradiation of human fibroblast cultures extended their lifespan by one-quarter (655); this was not accompanied by specific chromosome abberations or activation of telomerase (655). Furthermore, in a large study involving 900 mice, Caratero et al (656) demonstrated that low-dose irradiation (25-50-fold background) resulted in a significant increase in longevity compared to the control group (673 days compared to 549 days for 50% survival of the starting population). Moreover, in C. elegans, the mutations conferring extended longevity also confer resistance to stress; and the same is true for the recently discovered trk-1 gene, overexpression of which can increase lifespan by up to 100% (657).…”
Section: Stressmentioning
confidence: 99%
“…3) Several kinds of effects of low-dose radiation on living organisms have been recognized; these include stimulation of the growth rate, 4) tumor progression, 5) activation of immune function, 6) suppression of reactive oxygen species (ROS)-related diseases, 7) resistance to high-dose irradiation, 8) and prolongation of life span. 9) However, the mechanisms underlying these responses remain obscure. It has recently been postulated that some of the effects could result from activation of the antioxidant defense system.…”
mentioning
confidence: 99%
“…Although some research groups have recently reported the effects of low doses of radiation on longevity and senescence (17,32,33), the underlying molecular mechanisms remained unknown. We thus focused on the mechanisms by which low doses of ionizing radiation inhibit cellular senescence.…”
Section: Discussionmentioning
confidence: 99%
“…These events result from alterations in differential signal transduction pathways. Recently, one research group reported that low doses of ionizing radiation enhanced longevity in mice and pigs (17), whereas another group reported that replicative senescence was induced by X-ray irradiation of normal human dermal fibroblasts (18) and human lung carcinoma cells of the H1299 line (19), implying a relationship between low-dose irradiation, aging and cellular senescence. More work in this area is needed.…”
Section: Introductionmentioning
confidence: 99%